Selective autophagy of RIPosomes maintains innate immune homeostasis during bacterial infection. (11th October 2022) - Mehto, Subhash; Jena, Kautilya Kumar; Yadav, Rina; Priyadarsini, Swatismita; Samal, Pallavi; Krishna, Sivaram; Dhar, Kollori; Jain, Ashish; Chauhan, Nishant Ranjan; Murmu, Krushna C; Bal, Ramyasingh; Sahu, Rinku; et al.
Abstract: The NOD1/2‐RIPK2 is a key cytosolic signaling complex that activates NF‐κB pro‐inflammatory response against invading pathogens. However, uncontrolled NF‐κB signaling can cause tissue damage leading to chronic diseases. The mechanisms by which the NODs‐RIPK2‐NF‐κB innate immune axis is activated and resolved remain poorly understood. Here, we demonstrate that bacterial infection induces the formation of endogenous RIPK2 oligomers (RIPosomes) that are self‐assembling entities that coat the bacteria to induce NF‐κB response. Next, we show that autophagy proteins IRGM and p62/SQSTM1 physically interact with NOD1/2, RIPK2 and RIPosomes to promote their selective autophagy and limit NF‐κB activation. IRGM suppresses RIPK2‐dependent pro‐inflammatory programs induced by Shigella and Salmonella . Consistently, the therapeutic inhibition of RIPK2 ameliorates Shigella infection‐ and DSS‐induced gut inflammation in Irgm1 KO mice. This study identifies a unique mechanism where the innate immune proteins and autophagy machinery are recruited together to the bacteria for defense as well as for maintaining immune homeostasis. Synopsis: Bacterial infection induces the formation of RIPosomes (RIPK2 oligomers) that are recruited to the bacteria to enhance the NF‐κB response. To maintain innate immune homeostasis, RIPosomes undergo selective autophagy mediated by autophagy proteins, IRGM, and p62/SQSTM1. RIPosomes are self‐assembling structures that are formed upon bacterial infection and coat bacteria to induce NF‐κB response. IRGM‐ and p62‐mediated selective autophagy degrades NODs, RIPK2, and RIPosomes to suppress NF‐κB response. IRGM suppresses RIPK2‐dependent NF‐κB and interferon responses upon Shigella ‐ and Salmonella infection. RIPK2 inhibition using GSK583 ameliorates shigellosis‐ and DSS‐induced gut inflammation in Irgm1KO mice Abstract : Bacterial infection induces the formation of RIPK2 oligomers that coat the bacteria to enhance NF‐κB response, a process that is counteracted by selective autophagy of RIPK2 oligomers.